Cefiderocol for Carbapenem-Resistant Bacteria: Handle with Care! A Review of the Real-World Evidence - Pasquale Sansone; Luca Gregorio Giaccari; Francesco Coppolino; Caterina Aurilio; Alfonso Barbarisi; Maria Beatrice Passavanti; Vincenzo Pota; Maria Caterina Pace (MDPI AG, 2022)
(1) Background: healthcare-associated infections are one of the most frequent adverse events in healthcare delivery worldwide. Several antibiotic resistance mechanisms have been developed, including those to carbapenemase. Cefiderocol (CFD) is a novel siderophore cephalosporin designed to treat carbapenem-resistant bacteria. (2) Methods: we performed a systematic review of all cases reported in the literature to outline the existing evidence. We evaluated real-world evidence studies of CFD in the treatment of carbapenem-resistant (CR) bacteria. (3) Results: a total of 19 publications treating cases of infection by CR bacteria were included. The three most frequent CR pathogens were Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae. A regimen of 2 g every 8 h was most frequently adopted for CFD with a mean treatment duration of 25.6 days. CFD was generally well tolerated, with fewer side effects. The success rate of CFD therapy was satisfactory and almost 70% of patients showed clinical recovery; of these, nearly half showed negative blood cultures and infection-free status. (4) Conclusions: This review indicates that CFD is active against important GN organisms including Enterobacteriaceae, P. aeruginosa, and A. baumannii. CFD seems to have a safe profile.